Urinary tract stones and well water consumption in patients at Zaenoel Abidin Hospital Banda Aceh - Mulia, Vera Dewi; Ismy, Jufriady; Lusmianda, Rudy; Suardi, Hijra Novia; Suryawati, Suryawati (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Background: Several remote areas in Aceh lack proper water supply, leading to the citizens to consuming well water for daily needs. The water quality is determined by the concentration of minerals thus affected by location sources. Insufficient monitor of its quality poses risks of health problems, such as urinary tract stones. Objective: This study investigated the incidence of urinary tract stones on patients seeking medical help in Zaenoel Abidin hospital and its association to well water consumption. Methods: Respondents were patients visiting the urological surgery polyclinic at Zaenoel Abidin Regional Hospital and consenting to be research respondents. Sixty respondents were divided into two groups: the patient group suffering from urinary tract stones and those who did not. The disease status was determined based on the diagnosis of a urology specialist and the results of ultrasonography. Analysis of the relationship between well water consumption and the emergence of disease was analyzed statistically. Results: the majority of respondents were from out the city’s capital (Banda Aceh) (48, 80%), men (43, 71.1%), and 45 to 65 years old. Among the patients suffering from urinary tract stones, most of them (63.6%) consumed well water, while only a few of the control group, non-urinary tract stones patients, (36.4%) consumed well water. There is a relationship between well water consumption and the risk of disease (p = 0.038, OR = 3.5) Conclusion: The use of well water for daily water intake contributes to developing urinary tract stones.